Interaction of Turkey and World Trade within the Framework of the World Trade Organization - Aytüre, Selma; Yücel, Ahmet (International Journal of Scientific Research and Management (IJSRM), 2021)
The level and direction of the relationship between WT (World Trade) and TFT (Turkey Foreign Trade) statistically analysed in this study. For this purpose, in addition to some descriptive statistics, correlation and regression algorithms were utilized to observe the relationship. In addition, point, box and line graphs were used to observe the relative distributions of WT and TFT. According to the results, there is a 99.258 % correlation between WT and TFT. In addition, a linear regression model was designed in which TFT was determined as dependent and WT was determined as independent variable. The model is statistically significant at a confidence level of 0.05 and R, R-square and adj.-R-square explanatory ability rates of the model are 99.2 %, 98.5 % and 98.4 %, respectively. The scatter-plot shows that the binary value points are generally distributed around the linear line. In the box-plot, it is observed that WT has a wider range than TFT, but generally both variables have a symmetrical distribution. Finally, the line graph shows the ordered and consequetive 38-year distribution of both variables. Although the distribution is generally parallel to each other, the upward movement of WT has been observed to be sharper and accelerated in the last 10 years. All these results indicate that TFT has a very strong level of relationship with WT and that WT can be used as an important parameter in understanding TFT.